Glutamate protects neuromuscular junctions from deleterious effects of β‐amyloid peptide and conversely: An in vitro study in a nerve–muscle coculture. Issue 4 (9th December 2014) - Combes, Maud; Poindron, Philippe; Callizot, Noelle
Abstract : Murine models of Alzheimer's disease with elevated levels of amyloid‐β (Aβ) peptide present motor axon defects and neuronal death. Aβ1–42 accumulation is observed in motor neurons and spinal cords of sporadic and familial cases of amyotrophic lateral sclerosis (ALS). Motor neurons are highly susceptible to glutamate, which has a role in ALS neuronal degeneration. The current study investigates the link between Aβ and glutamate in this neurodegenerative process. Primary rat nerve and human muscle cocultures were intoxicated with glutamate or Aβ. Neuromuscular junction (NMJ) mean size and neurite length were evaluated. The role of N‐methyl‐D‐aspartate receptor (NMDAR) was investigated by using MK801. Glutamate and Aβ production were evaluated in culture supernatant. The current study shows that NMJs are highly sensitive to Aβ peptide, that the toxic pathway involves glutamate and NMDAR, and that glutamate and Aβ act in an interlinked manner. Some motor diseases (e.g., ALS), therefore, could be considered from a new point of view related to these balance disturbances. © 2014 Wiley Periodicals, Inc.